Pengaruh Aktivitas Seni Tari terhadap Peningkatan Kebugaran Jasmani: Tinjauan Literatur Sistematis - Muhammad Fikri; Auliana Mukhti Maghfirah; Wahida Wahyuni; Bram Sujadesman (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This study aims to examine the role of dance activities in improving physical fitness based on a review of recent literature. The method employed is a systematic literature review of various empirical studies related to dance activities and components of physical fitness. The findings indicate that dance activities significantly contribute to improvements in cardiorespiratory capacity, muscle strength, flexibility, coordination, and body balance. Several studies report that structured dance exercises, such as Zumba, can significantly enhance aerobic endurance and dynamic balance. Furthermore, among the elderly, dance programs have been shown to effectively improve gait patterns, body stability, and muscle strength. Variations in dance types also influence fitness outcomes, with modern dance tending to have a greater impact compared to other forms, while traditional dance demonstrates advantages in certain contexts, even surpassing conventional exercises such as moderate jogging. Moreover, the integration of dance movements into fitness programs, such as traditional dance-based exercise routines, has proven effective in enhancing multiple components of physical fitness and holds strong potential for application in physical education. Overall, these findings confirm that dance can serve as an effective alternative or complement to conventional exercise, while also embodying cultural values that support the preservation of local wisdom